2002
DOI: 10.1179/joc.2002.14.4.412
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Monitoring Response to Chemotherapy Based on the Detection of Circulating Cancer Cells: A Case Report

Abstract: We describe a novel method for detecting micrometastasis in the blood stream of cancer patients based on RT-PCR amplification of tumor-associated carcinoembryonic antigen (CEA) mRNA. To increase sensitivity and specificity of RT-PCR, CEA transcript was selectively up-regulated in cancer cells by exposure of peripheral blood to non-toxic concentrations of staurosporine (ST). Thereafter, polyA(+) RNA was extracted from tumor cells captured by means of magnetic beads coated with a monoclonal antibody against a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Micrometastatic bone marrow tumor cells were successfully evaluated for the control of systemic therapy in breast cancer [18] as well as in recent colon cancer study [22]. A recent human breast cancer study showed that circulating tumor cells are significant independent prognostic factors [23].…”
Section: Discussionmentioning
confidence: 99%
“…Micrometastatic bone marrow tumor cells were successfully evaluated for the control of systemic therapy in breast cancer [18] as well as in recent colon cancer study [22]. A recent human breast cancer study showed that circulating tumor cells are significant independent prognostic factors [23].…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro experiments on human colorectal cancer cells demonstrated that this antimetabolite is able to substantially increase the expression of CEA epitopes on the tumor cell membrane in vitro [ 113 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. This effect has been exploited to facilitate the detection of circulating colon cancer cells in patients [ 163 , 164 ]. In the case of melanoma cells, treatment in vitro with 5-FU sensitized cells to lysis induced by cytotoxic CD8+ T cells (CTL) recognizing the G209 antigen [ 165 ].…”
Section: Drug-induced Upregulation Of Tumor Immunogenicitymentioning
confidence: 99%
“…For chemotherapy management, some reports with limited patient numbers, have suggested that variations in CTC counts may be associated with treatment response [104]. For this application, the cytological CellSearch® technique has achieved very strong evidence, with several studies published on metastatic colorectal cancers ( Table 2).…”
Section: Ctcsmentioning
confidence: 99%